High-frequency induction-heated consolidation of nanostructured WC and WC-Al hard materials and their mechanical properties. (April 2017) - Shon, In-Jin
Abstract: The rapid sintering of nanostructured WC-Al composites in a short time was investigated with a focus on the mechanical properties (hardness and fracture toughness) and consolidation using high-frequency induction heated sintering. This process allowed very quick densification to near theoretical density and prohibited grain growth in the nano-materials. The addition of Al to WC facilitated consolidation and improved fracture toughness. The hardness and fracture toughness of WC with 5 vol.% Al and WC with 10 vol.% Al composites were higher than those of monolithic WC. Highlights: Nearly full-dense nanostructured WC-Al composites were obtained within 2 min. The starting temperature of rapid densification of WC was remarkably reduced by the addition of Al. The hardnesses of WC-5 vol.% Al and WC-10 vol.% Al were higher than that of monolithic WC due to refinement of WC grains. The fracture toughness of WC increased with increased Al content. The use of Al instead of Co or Ni effectively maintained the high hardness of monolithic WC.